Energy-efficient clustering: optimal cluster head location algorithms accounting for prohibited region in wireless sensor networks - Shi, Guang (Nanyang Technological University, 2023)
This dissertation focuses on the optimization of Wireless Sensor Networks in the presence of prohibited regions, addressing the minimization of energy consumption. Previous studies did not consider real-world scenarios with prohibited areas. This work provides further proof for the optimal CH positions within prohibited regions under different transmission models. We introduce the Single Cluster Head Allocation with Prohibited Region Algorithm and Multi Cluster Head Allocation with Prohibited Region Algorithm, which efficiently and accurately determines the optimal CH positions in single-cluster and multi-cluster WSNs considering forbidden zones. Theoretical analysis and simulation results validate the effectiveness and superiority of these proposed algorithms, providing a useful benchmark for evaluating distributed clustering schemes in WSNs with prohibited regions. Overall, this work contributes to a more realistic understanding of energy consumption problems in WSNs and enhances existing algorithmic solutions.